2020
DOI: 10.22270/ujpr.v5i2.388
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Intestinal Parasitic Infections Among Schoolchildren in Ibb City-Yemen

Abstract: Objectives:  Intestinal parasitic infections are widely distributed and remain one of the most health problems in Yemen. This is a cross-sectional study aimed to determine the prevalence of intestinal parasitic infection and associated factors among schoolchildren in Ibb City, Yemen. Methods:  A total of 300 stool samples were collected from schoolchildren between January to April 2018 and examined by direct smear and formalin ether concentration techniques. Results:  The result showed that 62.7% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 11 publications
9
11
2
Order By: Relevance
“…These findings necessitate providing school-based health education and implementing the MDA with albendazole together. Schoolchildren whose fathers are unemployed had higher infection rate of ascariasis, which was in agreement with previous studies conducted in Yemen [ 16 , 31 ], Ethiopia [ 32 ], Ghana [ 33 ] and Nigeria [ 34 ]. This finding may be attributed to those unemployed fathers who most often work in agricultural fields with a probability of accompanying their children during the work, a common practice in the rural areas of Yemen, and exposing them to contaminated soil.…”
Section: Discussionsupporting
confidence: 92%
“…These findings necessitate providing school-based health education and implementing the MDA with albendazole together. Schoolchildren whose fathers are unemployed had higher infection rate of ascariasis, which was in agreement with previous studies conducted in Yemen [ 16 , 31 ], Ethiopia [ 32 ], Ghana [ 33 ] and Nigeria [ 34 ]. This finding may be attributed to those unemployed fathers who most often work in agricultural fields with a probability of accompanying their children during the work, a common practice in the rural areas of Yemen, and exposing them to contaminated soil.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, it was revealed that the prevalence of Giardia for males was 60.3% higher compared to the female by 47.5%, and likewise, a high percentage of Giardia infection was recorded in previous studies among males in Yemen; it was between 17-17.6% in Sana'a 7,11 and 32.1% in Ibb 8 . In contrast, Qasem et al, 13 noted that the high prevalence of Giardia was 64.4% among females. The higher prevalence of the Giardia infection among males in this work than females is due to the males in the study area are contributing to some works and they remain for a long time outside the home daily making them more susceptible to Giardia infection than females.…”
Section: Discussionmentioning
confidence: 88%
“…infection was (18.6%) recorded among less than 10 years. Qasem et al, 13 also reported that the age group of 9-12 years was 51.1% highly infected by G.…”
Section: Discussionmentioning
confidence: 91%
“…Inconsistent with other studies, Giardia duodenalis had the highest infection rate (17.7%), followed by Entamoeba histolytica / dispar (17.1%) [ 16 ]. In addition, in other studies, the highest IPIs among children were from Hadhramout; the main infective parasites were Giardia lamblia (19.2%) [ 38 ], and the second infection was in Ibb (23.6%) [ 39 ], followed by Saber camp, Lahaj governorate, Yemen (19.7%) [ 40 ]. In contrast, a lower G. lamblia infection rate of 3.0% was reported among children 3.0% from Al-Mahweet [ 29 ].…”
Section: Discussionmentioning
confidence: 99%